Effectiveness of newspaper advertising for patient recruitment into a clinical trial. (June 2014) - Hapca, Adrian; Jennings, Claudine G.; Wei, Li; Wilson, Adam; MacDonald, Thomas M.; Mackenzie, Isla S.
<x xml:space="preserve">Abstract</x> Aims To measure the impact of newspaper advertising across Scotland on patient interest, and subsequent recruitment into the Standard Care vs. Celecoxib Outcome Trial (SCOT), a clinical trial investigating the cardiovascular safety of non‐steroidal anti‐inflammatory drugs in patients with osteoarthritis or rheumatoid arthritis. Methods Newspaper advertisements about the SCOT trial were placed sequentially in regional and national Scottish newspapers. The number of phone calls as a result of exposure to the advertisements and ongoing study recruitment rates were recorded before, during and after the advertising campaign. To enroll in SCOT individuals had to be registered with a participating GP practice. Results The total cost for the advertising campaign was £46 250 and 320 phone calls were received as a result of individuals responding to the newspaper advertisements. One hundred and seventy‐two individuals were identified as possibly suitable to be included in the study. However only 36 were registered at participating GP practices, 17 completed a screening visit and 15 finally were randomized into the study. The average cost per respondent individual was £144 and the average cost per randomized patient was £3083. Analysis of recruitment rate trends showed that there was no impact of the newspaper advertising campaign on increasing recruitment into SCOT. Conclusions Advertisements placed in local and national newspapers were not an effective recruitment strategy for the SCOT trial. The advertisements attracted relatively small numbers of respondents, many of whom did not meet study inclusion criteria or were not registered at a participating GP practice.